IMPLEMENTASI MANAJEMEN PROGRAM TAHFIDZ DALAM MENINGKATKAN KUALITAS HAFALAN SISWA - Vradinta Halizanindya; Muhlil Musolin; Mohamad Madum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Ma’arif Nurul Jannah State Elementary School has implemented the Al-Qur’an memorization program, which was established since the school was faunded in 2014. This study aims to describe and analyze how the implementation of management in the Al-Qur’an memorization program improves the quality of memorization at Ma’arif Nurul Jannah Elementary School, Janten. This study employed a qualitative researgh method with a phenomenological approach. Researchers observed the phenomena occurring at Ma’arif Nurul Jannah Elementary School, Temon, Kulon Progo through observation, interviews, and documentation. Data collection techniques included data reduction, data presentation and data verification to ensure data validity. Through and studies conducted by researchers, it was found that the implementation of management in the Tahfidz Al-Qur’an program at SD Ma’arif Nurul Jannah Janten was carried out though several management programs and several methods. The program is implemented by determining goals, targets, grouping of teachers and students as well as evaluation carried out by means of exams indicating results. As for the quality of students’ memorization with fluency, the suitability of tajwid and makhrah has been able to improve in this case by looking at the results of the final exam. Therefore, Ma’arif Nurul Jannah Janten Elementary School implements a comprehensive tahfidz management system so that the memorization process is balanced and produces results but also understands and practices the Qur’an.